Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1061/(asce)0742-597x(2010)26:1(9)
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resources and Strategies on Construction Company Performance

Abstract: Globalized competition and customer needs forced construction companies to measure their performance beyond the financial measures such as profitability, turnover, etc. As qualitative determinants were added to measurement systems, their investigation and evaluation became a major area of research. In this study, the impact of "resources and capabilities," "strategic decisions," "project management competencies," and "strength of relationships with other parties" on "company performance" was investigated. A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 57 publications
2
43
0
6
Order By: Relevance
“…Some theories and previous studies are becoming the basic of this research conceptual model, those are Absah (2008) [18], Isiket al (2010) [10] dan Huda & Wibowo (2013) [25]. The research of Absah (2008) [18] showed that, the competence of corporation gives a strong influence to the performance and competitiveness, also the performance comes from particular resources and competence.…”
Section: Research Model a Conceptual Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Some theories and previous studies are becoming the basic of this research conceptual model, those are Absah (2008) [18], Isiket al (2010) [10] dan Huda & Wibowo (2013) [25]. The research of Absah (2008) [18] showed that, the competence of corporation gives a strong influence to the performance and competitiveness, also the performance comes from particular resources and competence.…”
Section: Research Model a Conceptual Modelmentioning
confidence: 99%
“…The research of Absah (2008) [18] showed that, the competence of corporation gives a strong influence to the performance and competitiveness, also the performance comes from particular resources and competence. Meanwhile, the research from Isiket al, (2010) [10] dan Huda & Wibowo (2013) [25] concludes that (a) project management competence has a big deal in corporations' resources and capability, (b) project management competence has a significant influence towards corporation's performance, (c) Resource and performance have a significant influence towards the corporation's performance. Based on the former researches, the conceptual model has been drawn as in Figure 1.…”
Section: Research Model a Conceptual Modelmentioning
confidence: 99%
See 3 more Smart Citations